An Observatory of Groundwater in Crystalline Rock Aquifers Exposed to a Changing Environment: Hyderabad, India. Issue 1 (29th November 2018) - Maréchal, Jean-Christophe; Selles, Adrien; Dewandel, Benoit; Boisson, Alexandre; Perrin, Jérôme; Ahmed, Shakeel
Abstract : Core Ideas: Long‐term observatories allow the study of global changes to water resources in India. Crystalline rock aquifers are highly heterogeneous. Management of crystalline aquifers necessitates solving several scientific questions. A multidisciplinary approach is necessary for improving water management in India. Multiscale and long‐term work is needed to tackle the scientific challenges found in areas vulnerable to climate change and anthropic pressure. This is the case in the semiarid and drought‐prone regions of southern India where freshwater is scarce and agriculture near fast‐growing cities is triggering high water demand. The Indo‐French Center for Groundwater Research (IFCGR) was established in 1999 between the Indian National Geophysical Research Institute (NGRI) and the French Geological Survey (BRGM) at the NGRI campus in Hyderabad, India. For almost 20 yr, the IFCGR has studied the hydrodynamic properties and associated hydrological processes in crystalline aquifers. To that end, the Center set up two sites for observing groundwater in crystalline rock aquifers: (i) the Maheshwaram basin for the study of groundwater management at catchment scale, and (ii) the Choutuppal experimental site for the detailed study of hydrogeological processes at local scale (between wells). Multiscale approaches allow the characterization of hydrodynamic and transport properties of the shallow weathered part of such crystalline aquifers and the implications for groundwater management under overexploitation conditions. The objective is to provide suitable characterization of aquifer properties for developing modeling and management tools applicable to such heterogeneous aquifers.